2021
DOI: 10.1002/cam4.4443
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs to predict postoperative recurrence in bladder cancer and to develop a new molecular classification system

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This innovative approach can improve clinical decision making and, ultimately, enhance patient outcomes. 116 He et al found that patients diagnosed with postoperative recurrence of prostate cancer had high levels of serum miR-148a-3p and low levels of miR-485-5p. It has been demonstrated through receiver operating characteristic assessment that the concurrent measurements of miR-148a-3p and miR-485-5p are potential sensitive and specific diagnostic biomarkers for postoperative recurrence of prostate cancer.…”
Section: Postoperative Monitoring For Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…This innovative approach can improve clinical decision making and, ultimately, enhance patient outcomes. 116 He et al found that patients diagnosed with postoperative recurrence of prostate cancer had high levels of serum miR-148a-3p and low levels of miR-485-5p. It has been demonstrated through receiver operating characteristic assessment that the concurrent measurements of miR-148a-3p and miR-485-5p are potential sensitive and specific diagnostic biomarkers for postoperative recurrence of prostate cancer.…”
Section: Postoperative Monitoring For Recurrencementioning
confidence: 99%
“…developed a set of lncRNA markers as potential dependent molecular indicators for predicting early recurrence in individuals with muscle‐invasive bladder cancer. This innovative approach can improve clinical decision making and, ultimately, enhance patient outcomes 116 . He et al.…”
Section: Emerging Post‐surgical Tumor Treatment Technologiesmentioning
confidence: 99%